Importance of Upskilling and Reskilling in Educational Leadership and Management - Osias Kit T. Kilag; Katrine S. Padilla; Fedelyn S. Yorong; July Grace A. Merabedes (Journal of Learning on History and Social Sciences, 2024)
This research study investigates the impact of upskilling and reskilling initiatives for educational leadership and management on student learning outcomes, teacher retention, and school culture. The study involves a mixed-methods approach, which includes surveys, interviews, and document analysis, to gather data from educational leaders and teachers from various schools in the Philippines. The findings of the study reveal that upskilling and reskilling initiatives for educational leadership and management can have a positive impact on student learning outcomes, teacher retention, and school culture. The study identifies key competencies and skills necessary for effective educational leadership and management and highlights effective pedagogical approaches and training methods for upskilling and reskilling initiatives. Comparing the findings to previous studies, the research supports the idea that investing in upskilling and reskilling initiatives for educational leaders and teachers is crucial for improving student learning outcomes and school culture. Furthermore, the study suggests that a holistic approach that focuses on both technical and soft skills development is necessary for the success of upskilling and reskilling initiatives. In conclusion, this study provides valuable insights into the impact of upskilling and reskilling initiatives for educational leadership and management. The findings highlight the importance of investing in professional development for educational leaders and teachers to improve student learning outcomes, teacher retention, and school culture. The study provides practical recommendations for the design and implementation of upskilling and reskilling initiatives and suggests methods for measuring their impact. Ultimately, this research contributes to the growing body of literature on effective educational leadership and management and offers guidance for educational policymakers, administrators, and teachers seeking to improve their professional development programs.